Penerapan Konsep Healing Environment Pada Perencanaan Public Healing Center di Desa Batuan, Sukawati, Gianyar, Bali: Bahasa Indonesia - Ni Putu Cahaya Suksema Dewi; I Nyoman Gede Maha Putra; Made Suryanatha Prabawa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
A Public Healing Center is defined as a place or healing center for people with mental health disorders that involve the psychological effects of the patient in it. There are three approaches used in designing a healing environment, namely natural, sensory and psychological. The number of sufferers of mental health disorders in Indonesia is quite high, therefore it is necessary to have an environmental area for people with complaints or mental health disorders to be able to "healing" or healing their mental health. Mental health is still a taboo subject in Indonesian society, sometimes people with mental health complaints or disorders feel intimidated so they are reluctant to come or visit places such as psychologists. This condition further supports the urgency of providing mental health treatment facilities that can become a public forum without intimidation, an area of ​​education on how to empower individuals, families and the wider community to be able to maintain their mental health in dealing with any situation in their life. This Public Healing Center is a centralized and representative facility for healing people with mental health disorders with services and facilities that suit the needs of sufferers. It is hoped that in the future it will be able to reduce the number of sufferers of mental health disorders and make this facility a place for educating the wider community about the importance of maintaining mental health and of course suppressing the assumption of negative stigma towards sufferers of mental health disorders.